Gambaran Kecenderungan Perilaku Self-Harm Siswa Sekolah Menengah Pertama (SMP) - Ramadhan, Fatia Wina; Sukmawati, Indah; Ifdil, Ifdil; Wandha Putra, Febri (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
Abstract: The background of this study is the phenomenon of self-harm carried out by junior high school students to vent the emotional feelings felt due to the rapid changes in the process of adolescent self-development. This study aims to describe the tendency of self-harm behavior in students as reviewed from the types of major self-mutilation, stereotypic self-injury, and moderate self-mutilation. This study uses a quantitative approach with a descriptive method. The population in this study amounted to 4,399 students. Sampling was carried out using the Cluster Random Sampling method with a total sample of 370 students. The results showed that the average overall self-harm behavior reached a score of 61 (36.93%), indicating that the level of self-harm behavior tendency carried out by students in several junior high schools in Padang City was relatively very low. The forms of self-harm behavior carried out by students as reviewed from the type of major self-mutilation include reckless driving and ignoring the dose of medication consumed (overdose). In the type of stereotypic self-injury, the tendency of self-harm behavior carried out is hitting the chest and banging the head against the wall as an outlet for the emotions felt. While in the moderate self-mutilation type, students generally intentionally hurt themselves by scratching themselves and cutting their body parts. Based on the results of this study, counselors can provide assistance in the form of individual counseling services, as well as group counseling services in order to reduce the tendency of self-harm behavior.